Pengaruh Reward, Punishment, dan Budaya Organisasi terhadap Kinerja Mitra PT Hannas Fantastic Tour - Nur Aini; Shafitranata Shafitranata; Asri Winanti Madyoningrum; Ria Octavia (Reviu Akuntansi, Manajemen, dan Bisnis, 2023)
Purpose: Aim of this research is to analyse and measure the effect of reward, punishment, and organizational culture on the performance of PT Hannas Fantastic Tour partners both partially and simultaneously. Methodology/approach: This research uses quantitative methods with sampling using surveys supported by instruments in the form of questionnaires to all partners via google form. The sampling technique used was random sampling with a sample of 130 respondents. The analysis test uses multiple linear regression with descriptive analysis methods, classical assumption tests, and hypothesis testing. Results/findings: The results showed that partially, reward has no significant effect on performance; punishment has no significant effect on performance; organizational culture has a significant effect on performance. Simultaneously, reward, punishment, and organizational culture have a significant effect on performance. Limitations: The research measures the influence, the measurement is only carried out at one branch and not concluded the whole company. Contribution: The contribution of this research is to provide solutions to the welfare of company partners through providing clear work contracts so that partners have work attachments, it is expected to increase work productivity.